PENGARUH GAYA KEPEMIMPINAN DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PT. GLOBAL JET CARGO SURABAYA - Aoliya, Muhammad Aan (Jurnal Sosial Humaniora Sigli, 2023)
This study aims to determine the simultaneous effect and partial work ability of employees which include leadership style, promotion on employee performance at PT Global Jet Cargo Surabaya and determine the leadership style variable that has a dominant influence on employee performance at PT Global Jet Cargo Surabaya. The sample in this study were employees at PT Global Jet Cargo Surabaya, namely 98 employees. This type of research is explanatory research (explanation), that is, if the data is the same, the researcher explains the causal relationship between variables through hypothesis testing. The sampling technique used in this study is non-probability sampling, namely the entire population is used as the research sample. Data analysis using the F test and t test. The conclusion from the research results can be seen that there is influence of leadership style and promotion both simultaneously and partially on the performance of employees at PT Global Jet Cargo. Leadership style variable has a dominant influence on employee performance at PT Global Jet Cargo.Keywords: leadership style, promotion employee performance